Los cultivos celulares y de tejidos - Soto Escalona, Armando; Olivares, Gilberto (Investigación Clínica, 2013)
A review of different aspects of tissue culture methods is made, with discussion on basic requeriments of salts and nutritive substances important for keeping osmolarity, pH and life conditions in vitro. A description of the techniques used for culturing amnion cells, chick embryo fibroblasts and fetal human kidney cell is presented besides a brief outline of continuos culture of cell strains. Finally on explanation of uses of cell culture in Virology and Pharmacology is offered.